PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR DAN MOTIVASI SISWA MATA PELAJARAN MATEMATIKA - Ade Nor Isnanda; Aprilia Dwi Handayani; Bambang Agus Sulistyono; Choiruddin (STAI KH. Muhammad Ali Shodiq, 2024)
This research aims to find out how the discovery learning model is implemented, improving learning outcomes, and increasing learning motivation for grade 5 students at SDN Pule 2 for the academic year 2023-2024. The research subjects were 15 students of fifth grade at SDN Pule 2, and a mathematics teacher as observer. The data collected includes student observation results, student learning outcomes, student learning motivation questionnaire results. This research is Classroom Action Research which was carried out in two cycles. Each cycle includes four (4) stages, namely, planning, implementing actions, observation and reflection. In this research, it can be said to be successful if at least 80% of students have high motivation (≥50) and at least 80% of students get scores above the KKM (70). The research results showed: (1) Student learning motivation was high in cycle I at 73.33% with an average of 68.9 and in cycle II at 93.33% with an average of 83.83. (2) Student learning completeness in cycle I was 66.7% with an average of 72.67 and in cycle II it was 86.7% with an average of 88.67. From the data above, it clearly shows that in cycle I the level of student motivation and student learning outcomes were not in accordance with the indicators of success so it was continued to cycle II, whereas in cycle II the level of student motivation and student learning outcomes were in accordance with the indicators of success so the research was stopped in the cycle II.